Study of The Effect of Zeolite Catalyst Use on Renewable Energy Products from HDPE Plastic Pyrolysis - Fanani, Nurull; Novianarenti, Eky; Ningsih, Erlinda; Udyani, Kartika; Budianto, Agus; Tuhuloula, Abubakar (Journal of Applied Sciences, Management and Engineering Technology, 2020)
Nowadays, waste is a serious problem, especially plastic waste, which is quite alarming in the world. Plastic is waste that is difficult to degrade and takes hundreds of years to decompose. One of the promising technologies for recycling plastics is pyrolysis. This is the process of breaking long chains of polymers into hydrocarbons which are carried out at high temperatures. The purpose of this paper was to know the effect of using catalysts and non-catalysts on yield and calorific value. In this study, the pyrolysis process used a natural zeolite catalyst with a temperature of 500ÂºC. 50 grams of HDPE Plastic feed was put into the reactor for 3 hours. The variations in the addition of Zeolite catalyst were 1.5, 2.5, 3.75 and 5%wt. The results goals that the highest yield was 44.36% and the heating value of 10230.295 cal/g for the addition of 5 grams of catalyst. The addition of a catalyst can increase the conversion of plastic to fuelKeywords: Catalyst, Plastic, HDPE, energy, pyrolysis